SEMANTIC STRUCTURAL ANALYSIS OF SPEECH ACTS IN ENGLISH AND UZBEK LANGUAGES - Mohinur, Mohinur (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study conducts a semantic structural analysis of speech acts in English and Uzbek languages to explore the pragmatic functions, linguistic forms, and cultural influences shaping communication in diverse cultural contexts. Through qualitative and quantitative analyses, key findings reveal both similarities and differences in the realization of speech acts between the two languages. While both English and Uzbek employ a range of speech act types to achieve communicative goals, variations in linguistic forms and cultural connotations reflect cultural norms and social expectations.